Relationship Between Circulating Metabolic Hormones and Their Central Receptors During Ovariectomy-Induced Weight Gain in Rats - Burch, Kaitlin E.; McCracken, Kelly; Buck, Daniel J.; Davis, Randall L.; Sloan, Dusti K.; Curtis, Kathleen S. (Frontiers in Physiology, 2022)
Although increasing research focuses on the phenomenon of body weight gain in women after menopause, the complexity of body weight regulation and the array of models used to investigate it has proven to be challenging. Here, we used ovariectomized (OVX) rats, which rapidly gain weight, to determine if receptors for ghrelin, insulin, or leptin in the dorsal vagal complex (DVC), arcuate nucleus (ARC), or paraventricular nucleus (PVN) change during post-ovariectomy weight gain. Female Sprague-Dawley rats with ad libitum access to standard laboratory chow were bilaterally OVX or sham OVX. Subgroups were weighed and then sacrificed on day 5, 33, or 54 post-operatively; blood and brains were collected. ELISA kits were used to measure receptors for ghrelin, insulin, and leptin in the DVC, ARC, and PVN, as well as plasma ghrelin, insulin, and leptin. As expected, body weight increased rapidly after ovariectomy. However, ghrelin receptors did not change in any of the areas for either group, nor did circulating ghrelin. Thus, the receptor:hormone ratio indicated comparable ghrelin signaling in these CNS areas for both groups. Insulin receptors in the DVC and PVN decreased in the OVX group over time, increased in the PVN of the Sham group, and were unchanged in the ARC. These changes were accompanied by elevated circulating insulin in the OVX group. Thus, the receptor:hormone ratio indicated reduced insulin signaling in the DVC and PVN of OVX rats. Leptin receptors were unchanged in the DVC and ARC, but increased over time in the PVN of the Sham group. These changes were accompanied by elevated circulating leptin in both groups that was more pronounced in the OVX group. Thus, the receptor:hormone ratio indicated reduced leptin signaling in the DVC and PVN of both groups, but only in the OVX group for the ARC. Together, these data suggest that weight gain that occurs after elimination of ovarian hormones by ovariectomy is associated with selective changes in metabolic hormone signaling in the CNS. While these changes may reflect behavioral or physiological alterations, it remains to be determined whether they cause post-ovariectomy weight gain or result from it.